Impacto financiero y clínico de la ciclofosfamida y bendamustina en el tratamiento de cáncer en México - Irlanda Guadalupe Díaz Martínez; Víctor Florentino Castro Georgana; Daniel Alejandro Vázquez Cahuich; Juan José De la Cruz López; Kenia Paola García Jesús; María Teresa Flores Dorantes; Pascual Pedraza Montero (JOURNAL OF BASIC SCIENCES, 2026)
Cancer is a serious global health problem. Various oncological treatments allow patients to achieve better therapeutic outcomes. Cyclophosphamide and bendamustine are drugs used in different cancer treatments that can be evaluated through pharmacoeconomic studies, such as cost-minimization analysis. This study compared cost the associated with the use of cyclophosphamide and bendamustine through a pharmacotherapeutic and cost-minimization evaluation across different types of cancer, as well as a compilation of adverse reactions based on clinical records and reviewed articles. A decision tree was generated to compare annual costs, annual chemotherapy cycles, and potential shortages of both medications. The results demonstrate that the greater financial accessibility of cyclophosphamide is offset by the manifestation of severe adverse reactions. Consequently, the selection of the optimal regimen must be based on a balance that harmonizes cost, safety, tolerability, and drug availability.